Feedback en educación clínica - Ceccarelli Calle, Juan Francisco (2015)
The feedback is a central component of medical education. Regrettably, medical teachers often believe that provide adequate feedback to students, however, several studies show confl icting results. The aim of this paper is to review the main concepts associated to feedback in clinical education as part of the teaching–learning process.